(3TQM GdbUjOI GdhGVMI aj JLhjO GdaGJMIs - (3HQgGf GdOjf EHQGgje Hf CHj HcQ GdLYHQj,J (B687 (3g` s
(3ChdgG (B:s
(3hHYO agPg cdeGJ JTJed Ydi GdbUjOI GdeSeGg HGdhGVMI ai JLhjO GdaGJMI HMeOc QHi Chd GdfXe CHJOi hCgOi bHdGJi ddfHi eMeO hHYO aNP JLhjO Ce GdcJGH ci JahR HJUMjM GdUdGI aJgJOi s
(3BNQgG (B:s
(3aEf CfJ MbbJ GdPi bO PcQJg JHQ HaQV GdebQGI eSJO hdGQH EdG Gddg aGYHOg eNdUkG hUd Ydi NjQ GdHQjI CMeO JeJ HMeO Gddg heYhfJg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3YdjgG Jedcs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3bQGAGJ (B188 (3, (B189) s
Keywords: (3GdbQGAGJ hGdJLhjOs